Pulmonary tuberculosis epidemiology and genetics in Kazakhstan - Yerezhepov, Dauren; Gabdulkayum, Aidana; Akhmetova, Ainur; Kozhamkulov, Ulan; Rakhimova, Saule; Kairov, Ulykbek; Zhunussova, Gulnur; Kalendar, Ruslan; Akilzhanova, Ainur (Frontiers in Public Health, 2024)
Background Tuberculosis (TB) is a major public health emergency in many countries, including Kazakhstan. Despite the decline in the incidence rate and having one of the highest treatment effectiveness in the world, the incidence rate of TB remains high in Kazakhstan. Social and environmental factors along with host genetics contribute to pulmonary tuberculosis (PTB) incidence. Due to the high incidence rate of TB in Kazakhstan, our research aimed to study the epidemiology and genetics of PTB in Kazakhstan. Materials and methods 1,555 participants were recruited to the case–control study. The epidemiology data was taken during an interview. Polymorphisms of selected genes were determined by real-time PCR using pre-designed TaqMan probes. Results Epidemiological risk factors like diabetes (χ2 = 57.71, p < 0.001), unemployment (χ2 = 81.1, p < 0.001), and underweight-ranged BMI (<18.49, χ2 = 206.39, p < 0.001) were significantly associated with PTB. VDR FokI (rs2228570) and VDR BsmI (rs1544410) polymorphisms were associated with an increased risk of PTB. A/A genotype of the TLR8 gene (rs3764880) showed a significant association with an increased risk of PTB in Asians and Asian males. The G allele of the rs2278589 polymorphism of the MARCO gene increases PTB susceptibility in Asians and Asian females. VDR BsmI (rs1544410) polymorphism was significantly associated with PTB in Asian females. A significant association between VDR ApaI polymorphism and PTB susceptibility in the Caucasian population of Kazakhstan was found. Conclusion This is the first study that evaluated the epidemiology and genetics of PTB in Kazakhstan on a relatively large cohort. Social and environmental risk factors play a crucial role in TB incidence in Kazakhstan. Underweight BMI (<18.49 kg/m2), diabetes, and unemployment showed a statistically significant association with PTB in our study group. FokI (rs2228570) and BsmI (rs1544410) polymorphisms of the VDR gene can be used as possible biomarkers of PTB in Asian males. rs2278589 polymorphism of the MARCO gene may act as a potential biomarker of PTB in Kazakhs. BsmI polymorphism of the VDR gene and rs2278589 polymorphism of the MARCO gene can be used as possible biomarkers of PTB risk in Asian females as well as VDR ApaI polymorphism in Caucasians.